The Real‐World Observational Prospective Study of Health Outcomes with Dulaglutide and Liraglutide in Patients with Type 2 Diabetes (TROPHIES): Patient disposition, clinical characteristics and treatment persistence at 12 months. Issue 12 (31st August 2022) - Guerci, Bruno; Giorgino, Francesco; Sapin, Hélène; Boye, Kristina; Lebrec, Jérémie; Federici, Marco Orsini; Heitmann, Elke; Dib, Anne; Füchtenbusch, Martin; García‐Pérez, Luis‐Emilio
Abstract: Aims: The primary objective of the TROPHIES observational study is to estimate the duration of treatment on dulaglutide or liraglutide without a significant treatment change by 24 months in patients with type 2 diabetes (T2D) initiating their first injectable treatment with these glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs). This manuscript presents 12‐month interim data. Materials and Methods: TROPHIES is a prospective, non‐comparative, observational study of patients with T2D in Europe, naïve to injectable antihyperglycaemic treatments and initiating dulaglutide or liraglutide. Data on clinical characteristics, GLP‐1 RA persistence and treatment patterns of glucose‐lowering medication were collected at initiation of first injectable therapy and by 12 months. Results: By 12 months, 1014 dulaglutide and 991 liraglutide patients were eligible across France, Germany and Italy. Both cohorts presented a high probability [95% confidence interval (CI)] of GLP‐1 RA persistence [dulaglutide, 0.88 (0.86 to 0.90); liraglutide, 0.83 (0.80 to 0.85)] and reduction in mean glycated haemoglobin percentage (95% CI) from baseline [dulaglutide, −1.18 (−1.27 to −1.08); liraglutide, −1.15 (−1.26 to −1.05)] with 48.2% of dulaglutide and 41.2% of liraglutide patients reaching their individualized glycated haemoglobin percentage target set by the physician at baseline. Mean weight (95% CI) change from baseline was −3.2 kg (−3.6 to −2.8) for dulaglutide and −3.4 kg (−3.9 to −3.0) for liraglutide. Slight changes in concomitant medications were observed compared with baseline. Conclusions: In the real‐world setting, dulaglutide and liraglutide cohorts achieved good persistence with similarly improved glycaemic control that was accompanied by weight loss at 12 months, consistent with previous clinical trial results.